87.2k views
2 votes
-6(y+15)=3y+6 What value of Y makes the expression true?

User Cadvena
by
5.3k points

1 Answer

3 votes

Answer:

Explanation:

-6(y+15)=3y+6 Distribute the -6 on the right side of the equation

-6y-90=3y+6

Subtract 6 on both sides to cancel it out on the right side and get 3y by itself

-6y-90-6=3y+6-6

-6y-96=3y

Add 6y on both sides to cancel it out on the left so that -96 is on one side by itself

-6y+6y-96=3y+6y

-96=9y

Divide by 9 on both sides to get the value of y

-96/9=9y/9

y=-10.67

I keep getting the same answer sorry

User Ristorante
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.